How Do Companies Finance Their Acquisitions in UK? - Sethia, Lakshya (2009)
This research studies the mergers and acquisitions of publically listed bidder’s in the UK between the periods of 2001-2004. The study explores the various factors on which the bidder decides on the sources of financing the M&A. It explains the difference between the means of payment and the sources of financing. A widespread hand-collected dataset is used to see that the financing decision of the bidder is affected by the bidder/target and the deal features. The research uses univariate and multivariate analysis (tobit , logit , multinomial logit) to test the pecking order model, choice of financing for the growing firms and the importance of the value of the deal and bidder/target characteristics. firstly, if the information of the target is unavailable or if the target is large, then equity financing is preferred over cash and debt financing else cash/debt financing is used. Secondly, the analysis show that as per the pecking order model and the bidder’s favour to use internal cash financing first, which is also constant with the existing literature. Thirdly, the growing or developing firms usually prefer equity financing over other sources which is strongly revealed in the results. Finally, the results also show that various characteristics like the industry of target, form of acquisition, tender offer, hostile takeover and the target’s public status, all affect the bidder’s financing decision.